PEMANFAATAN MEDIA SMARTPHONE PADA SISWA/I KELAS VI SEKOLAH DASAR NEGERI 16 DI NAGARI SUPAYANG - Lili Rahminda; Refika Mastanora (KINEMA: Jurnal Komunikasi dan Penyiaran, 2023)
This study aims to find out how the use of smartphone media in Class VI students of SD Negeri 16 in supayang. The problem discussed in this study is the use of smartphone media in students of class VI in SD Negeri 16 supayang. The background to raising this issue is that many grade VI elementary school students in Nagari Agarng use smartphones to play online games such as pubg, mobile legend, and freefire and some use smartphones to play tiktok and Instagram. The type of research used is field research. To obtain data from the problems studied, the data collection technique used by researchers is through observation, interviews and documentation. From the research conducted by researchers in the field, it can be concluded that the use of smartphone media in students /I grade VI public elementary school 16 nagari agarng as a medium of information, giving personal identity, social interaction and integration.